O Palácio dos Marqueses de Alegrete à Mouraria: do Palácio ausente à memória do sítio - Câmara, Maria A. T. G. (2016)
Built by Manuel Teles da Silva (1641-1709), 2nd count of Vilar Maior and 1st Marquis of Alegrete, and named after his title, this sumptuous palace built near the Ferdinand Wall, stood out as an important Noble House in the context of the civil architecture of Lisbon, in the early 18th century. After a long and troubled life, due to the modifications caused by successive social and urban adaptations it would become finally demolished in 1946. In this article we propose to study this building, based on several collections, mainly in the municipal archives, in two specific moments: its foundation and initial construction, and the years that corresponded to its degradation and demolition, as well as those who dwelt in addition to its relationship with the surrounding urban area.